DETERMINAN PROFITABILITAS PADA PERUSAHAAN SUBSEKTOR PERTAMBANGAN BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2021 - Ami Yuliyanti; Lulu Amalia Nusron; Rahandhika Ivan Adyaksana; Ratna Purnama Sari (Jurnal Ekonomi Dan Bisnis, 2025)
This study targets to examine the impact of sales growth, inventory turnover, and working capital turnover on profitability of coal mining subsector companies. Indonesia's coal reserves are estimated to have a lifespan of 65 years. Coal is one of the main export commodities so it contributes greatly to Indonesia's economy. This research's method is quantitative by using secondary data. The coal mining subsector business listed in IDX during 2017 – 2021 period chosen as the population. The sampling approach used in this research is purposive sampling technique with the final number of samples as many as 14 companies. The data analysis approach used is multiple linear regression using SPSS 25 version. The final result of this research shows that sales growth partially has a positive effect on profitability, inventory turnover partially has a negative effect on profitability, and working capital turnover partially does not have an effect on profitability. This study's results also show that sales growth, inventory turnover, and working capital turnover simultaneously have a significant effect on profitability.